1976
DOI: 10.1002/mpo.2950020106
|View full text |Cite
|
Sign up to set email alerts
|

Mitomycin C in large infrequent doses in breast cancer

Abstract: Seventy-one women with far-advanced breast cancer resistant to standard chemotherapeutic agents were administered mitomycin C using an intermittent high dose schedule. One group consisted of 54 patients with measurable metastatic tumor; a second group consisted of 18 patients with nonmeasurable osseous metastases. Objective response rate in group 1 was 26% for an average duration of 2 1/2 months. Subjective response rate in group 2 was 44% for an average duration of 3 months. Response and toxicity data were si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1981
1981
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…MMC as a single agent achieves 30% of global re sponse [7][8][9][10][11] in patients not previously treated and 24.3% in previously treated cases [12], This indicates that the activity of this drug is similar to that of other agents used in advanced breast cancer. VBL has a 20% response rate when administered as intermittent bolus injections [13].…”
Section: Discussionmentioning
confidence: 95%
“…MMC as a single agent achieves 30% of global re sponse [7][8][9][10][11] in patients not previously treated and 24.3% in previously treated cases [12], This indicates that the activity of this drug is similar to that of other agents used in advanced breast cancer. VBL has a 20% response rate when administered as intermittent bolus injections [13].…”
Section: Discussionmentioning
confidence: 95%
“…Despite this reduction, hematologic toxicity re mained dose-limiting, and the weekly schedule yielded no advantages over the previously described daily schedule. Although response rates as high as 67% have been report ed [6], large reviews [2,7.8] of pooled data from multiple studies have placed the response rate to intermittently administered single-agent mitomycin in patients with metastatic breast cancer at between 26 and 38% (table 1) [6,[9][10][11][12][13][14][15]. Not surprisingly, for patients exposed to mul tiple prior chemotherapy regimens, the response rate has been lower, ranging from 15 to 25% [11,12,15].…”
Section: Single-agent Trialsmentioning
confidence: 99%
“…MMC, an antitumor antibiotic with alkylating activity, has demonstrated promising activity in MBC as a single agent, achieving objective response rates (ORRs) of approximately 35% and 25% in patients with chemo-naive and pretreated MBC, respectively [20][21][22][23]. MMC has also shown good efficacy in combination strategies for MBC; in a randomized phase III study in first-line MBC, epirubicin and MMC (EM) (± lonidamid) demonstrated at least equivalent efficacy, in terms of ORR, time to progression (TTP), OS, and tolerability compared with standard 5-FU/epirubicin/cyclophosphamide (FEC) [24].…”
mentioning
confidence: 99%